Experimental study on strength performance of soil reinforced with coconut fibre for PANCHOR–MUAR road - Tuan Ismail, Tuan Noor Hasanah; Yuriz, Yasmin; Hassan, Nurul Azida; Saji, Nurdalila; Wan Jusoh, Wan Amizah; A. Rahman, and Noor Khazanah (2021)
Laterite soil is a typical earthfill material used in road construction base and sub-base layers. Regrettably, such soil becomes soft and saturated under high water content and causes an unsatisfactory performance in withstanding loads from proposed structures. Recently, the use of fibres to improve the soil layer, thereby increasing its geotechnical properties, has been attracting worldwide attention. Therefore, the present study takes a holistic approach to utilise coconut fibre (CF) as sustainable fibre reinforcement to enhance the strength performance of local laterite soil at Panchor - Muar, Johor. It then is used as an earthfill material for construction work. This research focuses mainly on investigating the compaction parameters and bearing capacity of CF–laterite soil. Standard compaction test and California bearing ratio (CBR) test were performed on soil randomly included with three different CF proportions (0%, 0.5%, and 1.0%). Results indicate that the optimum moisture content increased and the maximum dry density decreased as the proportion of CF increased to 1.0%. The CBR value of the reinforced soil recorded a significant increase to 17.42% and 26.14% after being mixed with 0.5% and 1.0% CF proportions, compared with unreinforced soil (7.58%). The coconut fibrereinforcement makes the stabilised soil ideal as a subbase material for road pavement applications. In addition to enhancing soil strength efficiency, CF reuse would also reduce the amount of agricultural waste disposal to landfills and prevent environmental problems.